2009
DOI: 10.1002/mop.24161
|View full text |Cite
|
Sign up to set email alerts
|

Compact broadband 90° twist based on square waveguide section with two stepped corner ridges

Abstract: Compact rectangular waveguide 90° twist is studied. The twist transformer region is a square waveguide section with two stepped corner ridges. The twist can provide the 40‐dB return‐loss level over the rectangular waveguide operating band if the wide and narrow waveguide wall dimensions are in the ratio of 2:1. The twist lengths are less than the rectangular waveguide half‐wavelength at the central frequency of the chosen operating band. The design results are confirmed by the results of real device measuremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…For applications with size constraints, a waveguide of this length may not be practical and will have high insertion loss. The alternative design described by Rud et al [63] is compact and consists of overlapping rectangular apertures, as shown in Fig. B.1.…”
Section: B2 Design and Fabricationmentioning
confidence: 99%
See 1 more Smart Citation
“…For applications with size constraints, a waveguide of this length may not be practical and will have high insertion loss. The alternative design described by Rud et al [63] is compact and consists of overlapping rectangular apertures, as shown in Fig. B.1.…”
Section: B2 Design and Fabricationmentioning
confidence: 99%
“…Start with high-resistivity silicon. This appendix describes a micromachined compact 90 • twist that is based on a design first investigated by Rud et al [63]. The twist is designed to join a conventional WR-1.5 rectangular waveguide to a second, orthogonally-polarized waveguide, as illustrated in Fig.…”
Section: Appendix a Fabrication Processmentioning
confidence: 99%